Who is Responsible for the Resistance to the Advancement of Science? - Aragón, Luis Fernando (2023)
In this paper the resistance to the progress of science is briefly analyzed. The blame for suppressing the rapid advancement of science has traditionally been laid on various institutions such as the State (by not providing sufficient economic resources), and the Church (by opposing new treatments or procedures), or even the legitimate or unfounded fears of the population. Having recalled a few examples from the history of medicine, physiology, and astronomy, it is suggested that the main opposition to the progress of science necessarily comes from within its ranks. The need for a gradual questioning of novel ideas is justified while warning against excessive resistance. Some examples of resistance originating in religion are also presented, antagonism that may or may not be justified. Interestingly, in these examples, significant opposition from science itself has also been identified. In conclusion, the opposition to changing existing paradigms and embracing progress may be an inherent quality of science rather than a deficiency of religion or other institutions.